TEKNIK EDITING CROSS-CUTTING PADA FILM MENCURI RADEN SALEH SEBAGAI PEMBENTUK UNSUR DRAMATIK - Dedi Eko Nurcahyo (Institut Seni Indonesia Padangpanjang, 2025)
The film Mencuri Raden Saleh, an action-crime genre, successfully delivers a thrilling heist with tension and surprises in every scene. This research explores how the use of cross-cutting editing techniques shapes the four dramatic elements (conflicts, suspense, curiosity, and surprise) in the film using a qualitative descriptive approach. The analysis aims to identify the aspects contributing to the formation of these dramatic elements. The results show that the cross-cutting editing technique in Mencuri Raden Saleh is supported by precise editing tempo. This technique plays a crucial role in the film's key scenes as it enables the director to convey information across different locations, considering the numerous characters involved. Keywords: Cross-cutting, Dramatic Elements, Mencuri Raden Saleh.